The equation

$$(1-x^2)y'' - 2xy'+n(n+1)y = 0$$

is called Legendre's equation of order $n$.

I need to show that this equation of order $1$ has $y=x$ as one solution and then I need to use this to find the general solution for $x$ greater than $-1$ but less than $1$ (not inclusive)

  • $\begingroup$ Did you try to take $n=1$ and plug in $y(x) = x$ and see if it satisfies the equation? $\endgroup$ – Winther Jul 4 '16 at 1:39
  • $\begingroup$ if i plug that in there is still a y'' $\endgroup$ – mp12345 Jul 4 '16 at 1:43
  • $\begingroup$ and a y' in the equation $\endgroup$ – mp12345 Jul 4 '16 at 1:43
  • $\begingroup$ If $y(x) = x$ what is $y'(x)$ and $y''(x)$ ? In other words: what is the derivative of $x$ and the second derivative of $x$? $\endgroup$ – Winther Jul 4 '16 at 1:43
  • $\begingroup$ y'(x)=1 y''(x)=0 $\endgroup$ – mp12345 Jul 4 '16 at 1:44

Here is a solution using power series.

\begin{equation} (1-x^2)y'' - 2xy'+n(n+1)y = 0 \end{equation} Let $y=\sum_{k=0}^{\infty}c_kx^k$, $y^\prime=\sum_{k=1}^{\infty}kc_kx^{k-1}$, $y^{\prime\prime}=\sum_{k=2}^{\infty}k(k-1)c_kx^{k-2}$


\begin{equation} (1-x^2)\sum_{k=2}^{\infty}k(k-1)c_kx^{k-2}-2x\sum_{k=1}^{\infty}kc_kx^{k-1}+n(n+1)\sum_{k=0}^{\infty}c_kx^k=0 \end{equation}

\begin{equation} \sum_{k=2}^{\infty}k(k-1)c_kx^{k-2}-\sum_{k=2}^{\infty}k(k-1)c_kx^{k}-\sum_{k=1}^{\infty}2kc_kx^{k}+\sum_{k=0}^{\infty}n(n+1)c_kx^k=0 \end{equation}

\begin{equation} \sum_{k=0}^{\infty}(k+2)(k+1)c_{k+2}x^{k}-\sum_{k=0}^{\infty}k(k-1)c_kx^{k}-\sum_{k=0}^{\infty}2kc_kx^{k}+\sum_{k=0}^{\infty}n(n+1)c_kx^k=0 \end{equation} \begin{equation} \sum_{k=0}^{\infty}[(k+2)(k+1)c_{k+2}-k(k-1)c_k-2kc_k+n(n+1)c_k]x^k=0 \end{equation}


\begin{equation} (k+2)(k+1)c_{k+2}+(n(n+1)-k(k+1))c_k=0 \text{ for }k\ge0 \end{equation}

So \begin{equation} c_{k+2}=\frac{k(k+1)-n(n+1)}{(k+2)(k+1)}c_k \end{equation}

Solving for the coefficients $c_k$ of the solution yields $c_2=-c_0, c_3=0$. Thus all odd powers of the series greater than $1$ will have coefficient zero and the general solution will be of the form \begin{equation} y=c_1x+c_0(1-x^2+\cdots) \end{equation}

Therefore one linearly independent solution is $y_1=x$.

  • $\begingroup$ not sure if i can use power series or not but thanks for your time $\endgroup$ – mp12345 Jul 4 '16 at 2:21
  • $\begingroup$ I see that this is massive overkill. You only had to verify that $y=x$ is a solution and use reduction of order to find a second linearly independent solution. Nevermind. $\endgroup$ – John Wayland Bales Jul 4 '16 at 2:21
  • $\begingroup$ yes do you know how to show that second part? $\endgroup$ – mp12345 Jul 4 '16 at 2:27
  • $\begingroup$ Here is a good youtube explanation of the process of "reduction of order" you can use to find a second solution to a second order DE given a first solution. youtube.com/watch?v=oQSFW8BIrY0 $\endgroup$ – John Wayland Bales Jul 4 '16 at 4:20

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.